Peran Majelis Dikdasmen Dalam Peningkatan Kinerja Guru Di MTs Muhammadiyah Nangahure - Muhammad Ihsan Wahab; Agus Tinus (Jurnal Kebijakan dan Pengembangan Pendidikan, 2016)
Abstract: This research aims to describe the role of the Wiring branch primary and secondary education Council in improving teacher performance in MTs Muhammadiyah Nangahure. The research method used in this study is a descriptive qualitative approach. This research was conducted at MTs Muhammadiyah Nangahure, Wiring District. The subject of the research was the Muhammadiyah Branch Manager. Data collection techniques include observation, interview, and documentation. Data analysis techniques using Miles and Huberman (1992) in the form of reviewers, sorting, grouping data to compile work hypotheses and raise the theory of research results. Descriptive analysis is done by data reduction, data presentation, and concluding. The results of this study indicate that the role of the primary and secondary education assembly has proven ineffective. The ineffectiveness of the primary and secondary education assembly can be seen in two ways. First, because there is no structure in the organization of the primary and secondary education assembly which is shown through the management decree by the leader of the Wiring Branch Muhammadiyah. Second, there is no work program.Keywords: Council of primary and secondary education, Muhammadiyah, Teacher performance Abstrak: Penelitian ini bertujuan untuk mengetahui peran Majelis Dikdasmen cabang Wuring dalam Peningkatan kinerja guru di MTs Muhammadiyah Nangahure. Metode penelitian yang digunakan dalam penelitian ini adalah pendekatan kualitatif deskriptif. Penelitian ini dilakukan di MTs Muhammadiyah Nangahure Kecamatan Wuring. subyek penelitian adalah Pimpinan Cabang Muhammadiyah. Teknik pengumpulan data meliputi observasi, wawancara dan dokumentasi. Teknik analisis data menggunakan Miles and Huberman (1992) berupa penelaah, pengurutan, pengelompokan data dengan tujuan menyusun hipotesis kerja dan mengangkat teori hasil penelitian. Analisis deskriptif dilakukan dengan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa peran majelis dikdasmen terbukti tidak efektif. Ketidakefektifan majelis Dikdasmen tersebut dapat di lihat pada dua hal. Pertama, karena tidak adanya struktur dalam organisasi majelis dikdasmen yang di tunjukkan melalui SK kepengurusan oleh pimpinan Muhammadiyah Cabang Wuring. Kedua, belum adanya program kerja.Kata kunci: Majelis Dikdasmen, Muhammadiyah, Kinerja guru